Characterization of Antimicrobial Peptide Fraction Producing Lactobacillus spp. Based on LC/MS-MS and Determination of ACE-inhibitory Activity in Kefir - Didem Şahingil; Merve Atalay (Journal of Agricultural Sciences)
In the present study, bioactive properties such as ACE-I activity and antimicrobial activity of kefir using different Lactobacillus (Lactobacillus delbrueckii ssp. bulgaricus ATCC 11842, Lactobacillus helveticus ATCC 15009 and Lactobacillus plantarum ATCC 14917) on some pathogen and Gram-positive bacteria during 28 day-storage periods was investigated and proteolysis (RP-HPLC peptide profiles, RP-HPLC amino acid profiles) were studied. The antimicrobial activity was investigated in kefir extract and separated peptide fractions (<3 kDa, named F2) which were characterized by LC-MS/MS and precursor and product ions were determined. Antimicrobial activity has been observed against pathogenic bacteria such as Escherichia coli (E. coli) in all samples. But the results revealed that the F2 fraction separated from kefir manufactured using Lactobacillus had a stronger antibacterial effect than control samples. It was determined that the F2 fraction has antimicrobial activity against S. aureus, S. warneri 95052 and S. hominis. The ACE-I activity of samples A, B, C and K were 76.47%, 84.95%, 87.33% and 85.57%, respectively. In the kefir using Lactobacillus has increase of ACE-I activity and was significant (P<0.01). In this study, it was concluded that the using of adjunct Lactobacillus contributed to the functional value of kefir.